Bacterial Spectrum and Susceptibility patterns of Pathogens in ICU and IMCU of a Secondary Care Hospital in Kingdom of Saudi Arabia - Khan, Mumtaz Ahmad (International Journal of Pathology, 2018)
AbstractObjective: To evaluate the microbiological spectrum and susceptibility pattern of pathogens in intensive care unit(ICU) and intermediate care unit (IMCU) in a single medical center from June 2011 to May 2012.Study Design: Prospective descriptive study.Place and duration of study: The study was carried out at the Department of Microbiology, King AbdullahHospital Bisha, Kingdom of Saudi Arabia over a period of 12 months from June 2011 to May 2012.Materials and Methods: Antibiotic in vitro susceptibility data of predominant ICU and IMCU isolates during2011–12 were analyzed using WHONET program.Results: 335 Clinical isolates were analyzed. The frequencies of Gram-positive and Gram negative bacteria were15 % and 85% respectively. Acinetobacter spp, Klebsiella species and Pseudomonas species were the most common Gramnegative isolates, while Staph. aureus and Coagulase-negative staphylococci (CoNS) were the two leading Grampositive isolates. 81 % Acinetobacter spp were found Multidrug- Resistant. Three Acinetobacter spp were found panresistant. Extended-spectrum beta-lactamase (ESBL) producing Klebsiella Pneumoniae accounted for 57 % of allKlebsiella species isolates. 29% Pseudomonas aeruginosa were found resistant to Imipenem.Conclusion: The high incidence of reduced antibiotic susceptibility among Gram negative bacteria in ICUssuggests that more effective strategies are needed to control the selection and spread of resistant organisms.